Accelerated Intestinal Epithelial Cell Turnover Correlates with Stimulated BMP Signaling Cascade following Intestinal Ischemia–Reperfusion in a Rat - Ben-Shahar, Yoav; Abassi, Zaid; Kreizman Shefer, Hila; Pollak, Yulia; Bhattacharya, Udayan; Sukhotnik, Igor (European Journal of Pediatric Surgery, 2020)
Introduction Bone morphogenetic proteins (BMPs) are a family of proteins that regulate proliferation and differentiation of intestinal epithelial cells. The purpose of this study was to evaluate the role of BMP signaling following intestinal ischemia–reperfusion (IR) in a rat model.Materials and Methods Male Sprague-Dawley rats were divided into four experimental groups: Sham-24 and Sham-48 rats underwent laparotomy and were sacrificed 24 or 48 hours later, respectively; IR-24 and IR-48 rats underwent occlusion of superior mesenteric artery and portal vein for 30 minutes followed by 24 or 48 hours of reperfusion, respectively. Enterocyte proliferation and apoptosis were determined at sacrifice. BMP-related genes and protein expression were determined using real-time polymerase chain reaction, Western blot, and immunohistochemistry for 48 hours followed by IR.Results IR rats demonstrated a significant increase in BMP2 (twofold increase, p < 0.05), BMP4 (sevenfold increase), STAT3 (70% increase), BMPR1 (70% increase) messenger ribonucleic acid levels in jejunum and was accompanied by a significant increase in BMP2 and BMP4 protein levels in jejunum (sixfold increase) (Western blot) and upward increase in the number of BMP-positive cells (by immunohistochemistry) in jejunal (48% increase) and ileal (56% increase) villi compared with Sham-48 animals. Elevation in BMP2 and BMP4 levels was associated with increased rates of cell proliferation and increased cell apoptosis.Conclusion Forty-eight hours following intestinal IR in rats, BMP signaling pathway was stimulated. The increase in BMP signaling pathway activity correlates with accelerated cell turnover.
Keywords: intestinal ischemia–reperfusion; bone morphogenetic protein; stem cells; proliferation; apoptosis